Pop-up COVID-19 vaccination clinics for vulnerable groups in the Midlands - Fiona O'Reilly; Mark McLoughlin; Douglas Hamilton; Jimmy Todd (James Cook University, 2023)
Introduction: Roma, travellers and the homeless suffer from a higher risk of both COVID-19 infection and severe disease relative to the general population. The purpose of this project was to ensure as many members as possible from vulnerable groups in the Midlands availed of COVID-19 vaccines.Methods: Following on from successful testing of vulnerable populations in the Midlands of Ireland in March/April 2021, a collaboration of HSE Midland’s Department of Public Health, Safetynet Primary Care and the HSE Midlands Traveller Health Unit (MTHU) operated pop-up vaccination clinics in June/July 2021, targeting the same populations. Clinics delivered the first dose of the Pfizer/BioNTech COVID-19 vaccine, registering clients for second doses in Community Vaccination Centres (CVCs).Results: Thirteen clinics were hosted between 8 June 2021 and 20 July 2021, resulting in 890 first-dose Pfizer vaccinations delivered to vulnerable populations.Discussion: Trust established months prior with our grassroots testing service resulted in strong vaccine uptake, with the quality service provided seeding further demand over time. This service integrated into the national system and allowed individuals to receive their second doses within the community.